Association of sodium–glucose cotransporter-2 inhibitors with mortality across the spectrum of myocardial infarction: a systematic review and meta-analysis - Michele Maremmani; Ramin Ebrahimi; Marco Centola; Felice Achilli; Valentina Capone; Eduardo Bossone; Christian Templin; Davide Di Vece (Cardiovascular Diabetology)
Abstract Background The impact of sodium–glucose cotransporter-2 (SGLT2) inhibitors on mortality following myocardial infarction (MI) remains uncertain. Additionally, the role of type 2 diabetes mellitus (T2DM) and heart failure (HF) in modulating the effectiveness of these drugs post-MI are not fully understood. This meta-analysis aimed to assess the association of SGLT2 inhibitors with all-cause mortality in post-MI patients and to explore key moderators influencing this benefit. Methods PubMed, Embase, and Scopus were searched for randomized controlled trials (RTCs) and propensity score-matched (PSM) observational studies assessing SGLT2 inhibitors' impact on post-MI mortality. The primary outcome was all-cause mortality. We pooled hazard ratios (HRs) to estimate the intervention's effect on the overall population and stratified studies into early (SGLT2 inhibitors administered within eight weeks post-MI) and delayed treatment trials. Meta-regression assessed the moderating effects of T2DM and HF. Results  A total of five RCTs and four PSM observational studies involving 26,753 patients (mean [SD] age, 62.9 [10.5] years; 6,406 female [24.0%]; 16,369 T2DM [61.2%]; 13,933 HF [52.1%]) were included. Early and delayed treatment trials comprised 16,165 (60.4%) and 10,588 (39.6%) patients, respectively. SGLT2 inhibitors reduced all-cause mortality following MI (HR 0.79, 95% CI [0.68, 0.91]; p = 0.001; I2 = 59%). Stratified analysis demonstrated consistent effects in both early (HR 0.76, 95% CI [0.59, 0.98]; p = 0.03; I2 = 65%) and delayed (HR 0.81, 95% CI [0.67, 0.98]; p = 0.03; I2 = 60%) treatment. Meta-regression identified T2DM as a significant moderator of the mortality benefit (β = − 0.0049; p = 0.0006). Conclusion In this meta-analysis, early and delayed treatment with SGLT2 inhibitors following MI was associated with a significant reduction in all-cause mortality. Furthermore, the presence of T2DM was associated with a greater mortality reduction, while HF was not significantly associated with the outcome. Graphical Abstract Association of SGLT2 Inhibitors with Mortality Across the Spectrum of Myocardial Infarction. Data from 26,753 post-MI patients are summarized, including baseline characteristics. The plots represent the pooled hazard ratios (HRs) with 95% confidence intervals (CIs), comparing SGLT2 inhibitors to control (placebo/no treatment), with HRs below 1 favoring SGLT2 inhibitors. The diagram shows early and delayed treatment trial subgroups, presenting the number of participants, the percentage receiving SGLT2 inhibitors, and the respective HRs for mortality. The meta-regression panel highlights T2DM and HF as moderators, reporting β-coefficients (β), p-values, and residual heterogeneity (I2). Negative β (−) indicates that as the percentage of the moderator increases, the HR for mortality decreases. Abbreviations: HF, heart failure; MI, myocardial infarction; SGLT2i, sodium–glucose cotransporter-2 inhibitors; T2DM, type 2 diabetes mellitus.